Pêche Et Caractéristiques Morphologiques D’un Poisson-Chat Endémique Synodontis Punctifer (Daget, 1964) Dans Le Barrage Électrique De Taabo (Côte d’Ivoire) - Koffi, Hervé Oussou; Constance, Diaha N’guessan; Yaya, Soro; Konan, N’Da (European Scientific Journal, ESJ, 2018)
A study of Synodontis punctifer (family: Mochokidae) of Taabo Lake was conducted from October 2015 to September 2016. This was carried out so as to evaluate its quantity (biomass) caught by fishing and also its morphological characteristics. The fish were caught using gillnets at 4 sites of the lake and different measurements were made. The fishing effort was 23 to 11 fishermen / day in Taabo city, 17 to 11 fishermen / day in Courandjourou, 13 to 5 fishermen / day in Ahondo, and 8 to 3 fishermen / day in Taabo village. The catch per unit effort (CPUE) ranged from 17.7 to 3.7 g / fisherman / day, 9.2 to 1.2 g / fisherman / day, 8.3 to 0.7 g / fisherman /day, 8 to 1g / fisherman / day at Ahondo, Courandjourou, Taabo city and Taabo village, respectively. The overall annual production was estimated at 2199.3 kg, i.e. 817 kg (40%) at Ahondo, 788.3 kg (35%) at Courandjourou, 462.5 kg (20%) at Taabo, and 131.5 kg (5%) in Taabo village. The overall sex ratio (1: 1.33) was in favor of females. Individuals have negative allometric growth at all sites with values ranging from 1.72 to 2.89. The condition factor does not vary significantly between different categories of individuals (ANOVA, F = 2.79, p ˃ 0.05). A significant difference was observed between the average sizes of the individuals of the different sites (test, p˂0,05). The large size specimens were captured at Ahondo, mean (avg = 15.38 ± 1.68 cm FL). In Courandjourou, the sizes were intermediate (avg = 13.63 ± 1.64 cm LF). Smalls sizes have been observed in Taabo city (mean= 12.37 ± 1.24 cm FL) and Taabo village (mean= 15.58 ± 1.58 cm FL).